Student Religious Character and Islamic Culture in Elementary Schools of Sabang City's Tourism Zone - Husmayani, Husmayani; Basri, Hasan; Syahminan, Syahminan (Teunuleh Publisher, 2025)
This study aims to explore the implementation of religious character education among students in an elementary school located in the tourism area of Sabang City. Using a descriptive qualitative method, the research focuses on SD Negeri 25 Sabang, which actively incorporates Islamic values into its daily curriculum and school culture. The school emphasizes religious practices such as congregational prayers, Quran recitations, and social religious activities to strengthen students' moral development. Data were collected through observations, interviews with principals, Islamic education teachers, parents, and community leaders, and supported by relevant documentation. The findings show that students are able to maintain their Islamic identity despite strong exposure to foreign cultures brought by tourism. This resilience is achieved through the synergy of school programs, parental support, and active community involvement. Furthermore, students are trained to interact respectfully with tourists while upholding Islamic norms and values. The study concludes that a holistic, consistent, and community-supported religious education program is essential to build strong religious character among students living in multicultural environments influenced by globalization. These efforts contribute not only to preserving Islamic values but also to fostering a generation capable of adapting wisely to cultural diversity.